Map- or list-based recommender agents? Does the map metaphor fulfill its promise?. (October 2017) - Reitsma, Rene F.; Hsieh, Ping-Hung; Diekema, Anne R.; Robson, Robby; Zarske, Malinda
We present a spatialization of digital library content based on item similarity and an experiment which compares the performance of this spatialization relative to a simple list-based display. Items in the library are elementary school, middle school, and high school science and engineering learning resources. Spatialization and visualization are accomplished through two-dimensional interactive Sammon mapping of pairwise item similarities computed from the joint occurrence of word bigrams. The 65 science teachers participating in the experiment were asked to search the library for curricular items they would consider using as part of one or more teaching assignments. The results indicate that whereas the spatializations adequately capture the salient features of the library's content and teachers actively use them, item retrieval rates, task-completion time, and perceived utility do not significantly differ from the semantically poorer but easier to comprehend and navigate list-based representations. These results put into question the usefulness of the rapidly increasing supply of information spatializations.